MeshAndCollect: an automated multi‐crystal data‐collection workflow for synchrotron macromolecular crystallography beamlines. (1st November 2015) - Zander, Ulrich; Bourenkov, Gleb; Popov, Alexander N.; de Sanctis, Daniele; Svensson, Olof; McCarthy, Andrew A.; Round, Ekaterina; Gordeliy, Valentin; Mueller‐Dieckmann, Christoph; Leonard, Gordon A.
Abstract : Here, an automated procedure is described to identify the positions of many cryocooled crystals mounted on the same sample holder, to rapidly predict and rank their relative diffraction strengths and to collect partial X‐ray diffraction data sets from as many of the crystals as desired. Subsequent hierarchical cluster analysis then allows the best combination of partial data sets, optimizing the quality of the final data set obtained. The results of applying the method developed to various systems and scenarios including the compilation of a complete data set from tiny crystals of the membrane protein bacteriorhodopsin and the collection of data sets for successful structure determination using the single‐wavelength anomalous dispersion technique are also presented.